2005
DOI: 10.1159/000087361
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Cannabinoid Receptor Agonists Inhibit Neurogenic Inflammations in Guinea Pig Airways

Abstract: Background: Although neurogenic inflammation via the activation of C fibers in the airway must have an important role in the pathogenesis of asthma, their regulatory mechanism remains uncertain. Objective: The pharmacological profiles of endogenous cannabinoid receptor agonists on the activation of C fibers in airway tissues were investigated and the mechanisms how cannabinoids regulate airway inflammatory reactions were clarified. Methods: The effects of endogenous cannabinoid receptor agonists on electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…It should be noted, however, that in this study bronchoconstriction was induced by a calcium ionophore rather than capsaicin. In an in vitro study of guinea pig airway smooth muscle (Yoshihara et al, 2005), anandamide and palmitoylethanolamide inhibited contractions elicited by electrical field stimulation but not by neurokinin A, and also blocked capsaicincapsaicin-induced release of substance P-like immunoreactivity. These effects were selectively inhibited by a CB 2 but not a CB 1 antagonist, or by maxi-K ϩ channel blockers, suggesting that CB 2 agonists may have therapeutic value in asthma (Yoshihara et al, 2005).…”
Section: Cardiovascular and Respiratory Disordersmentioning
confidence: 93%
See 1 more Smart Citation
“…It should be noted, however, that in this study bronchoconstriction was induced by a calcium ionophore rather than capsaicin. In an in vitro study of guinea pig airway smooth muscle (Yoshihara et al, 2005), anandamide and palmitoylethanolamide inhibited contractions elicited by electrical field stimulation but not by neurokinin A, and also blocked capsaicincapsaicin-induced release of substance P-like immunoreactivity. These effects were selectively inhibited by a CB 2 but not a CB 1 antagonist, or by maxi-K ϩ channel blockers, suggesting that CB 2 agonists may have therapeutic value in asthma (Yoshihara et al, 2005).…”
Section: Cardiovascular and Respiratory Disordersmentioning
confidence: 93%
“…In an in vitro study of guinea pig airway smooth muscle (Yoshihara et al, 2005), anandamide and palmitoylethanolamide inhibited contractions elicited by electrical field stimulation but not by neurokinin A, and also blocked capsaicincapsaicin-induced release of substance P-like immunoreactivity. These effects were selectively inhibited by a CB 2 but not a CB 1 antagonist, or by maxi-K ϩ channel blockers, suggesting that CB 2 agonists may have therapeutic value in asthma (Yoshihara et al, 2005). In a recent study, inhibition of anandamide transport potently suppressed capsaicin-induced cough in mice, suggesting that the anandamide transporter may be a target for peripherally acting antitussive medications (Kamei et al, 2006).…”
Section: Cardiovascular and Respiratory Disordersmentioning
confidence: 93%
“…Pure ⌬ 9 -THC produces bronchodilation in asthmatic patients (329) and may have therapeutic value in asthma also by virtue of its anti-inflammatory effects (933). Indeed, in allergic airway disease induced in mice by aerosolized ovalbumin, pretreatment with ⌬ 9 -THC inhibits the expression of T-cell cytokines elicited by ovalbumin in the lungs and the associated inflammatory response (389).…”
Section: Asthmamentioning
confidence: 99%
“…Thus, inhibition of the electrically induced contraction of the guinea pig trachea is vanilloid-receptor mediated (Nieri et al 2003), whereas the sensory nerve-related activation of the guinea pig and human vagus nerve (Patel et al 2003) or the inhibition of electrically stimulated rat (Yousif and Oriowo 1999) and guinea pig airway contraction (Yoshihara et al 2004(Yoshihara et al , 2005 is CB 2 -receptor mediated. A CB 2 receptor has also been implicated in the inhibition of capsaicin-induced bronchoconstriction in some studies (Patel et al 2003;Yoshihara et al 2004Yoshihara et al , 2005. By contrast, other in vitro studies using electrically induced noradrenaline release (Vizi et al 2001) and in vivo studies using capsaicin-induced bronchoconstriction (Calignano et al 2000) reported an inhibitory effect of cannabinoids in the guinea pig in a rimonabant-sensitive and hence CB 1 -mediated manner.…”
Section: Other Peripheral Effectsmentioning
confidence: 99%
“…Cannabinoids can affect airway function in rats (Yousif and Oriowo 1999), guinea pigs (Calignano et al 2000;Yoshihara et al 2004Yoshihara et al , 2005, and humans (Patel et al 2003). Many of these effects are rimonabant insensitive and rather involve vanilloid or CB 2 receptors.…”
Section: Other Peripheral Effectsmentioning
confidence: 99%